The Multimethod Evaluation of a Curricular Intervention Intended to Reduce Sexual Violence on a College Campus: A Synthesis of Findings and Lessons Learned. Issue 2 (March 2023) - Lederer, Alyssa M.; Johnson, Katherine M.; Liddell, Jessica L.; Sheffield, Sydney
Sexual violence is a major problem on college campuses, and innovative solutions are needed. Our university created a semester-long, credit-bearing, academic course as a curricular intervention intended to reduce sexual violence on campus. In this article, we describe the multiple methods used to evaluate the course, including a pre–post online survey with a quasi-experimental design, a qualitative content analysis of student reflection papers, and semistructured interviews with previously enrolled students conducted by a peer interviewer 3 months after course completion. The synthesis of evaluation findings indicated that an academic course has the potential to positively affect campus climate around sexual violence. Furthermore, using multiple methods enabled us to create a theory of change that illustrates how key course components shaped students' knowledge, attitudes, and behaviors about sexual violence, thereby ideally generating campus change. Results have been used by various stakeholders for both practice-based and scholarly purposes. We provide lessons learned and implications for practice that are transferable to other multimethod curricular intervention evaluations regardless of topical focus, including the many ways in which using multiple methods added value to the study; the considerable investment of time and resources needed when using multiple methods; the challenges that can arise when integrating findings across methods; the major benefits of having a multidisciplinary research team consisting of faculty and students; and the need to engage in critical reflexivity.